Coupling coordination degree and influencing factors of green science and technology innovation efficiency and digital economy level: Evidence from provincial panel data in China - Mingkai, Zhang; Xinlan, Chen; Guangming, Yang (Frontiers in Environmental Science, 2023)
Green innovation and the digital economy are the new engine and driving force for Chinese high-quality development and will become the mainstream of China's high-quality development. Therefore, it is of great significance to explore the interaction between the two for the formulation of economic development policies. This paper constructed an evaluation system of green science and technology innovation efficiency (GSTIE) and digital economic level (DEL) based on 30 provinces in China. Through the corrected coupling coordination degree (CCD) model, this paper measured the CCD of GSTIE and DEL and analyzed its provincial differences and spatial effects. By employing the fuzzy set Qualitative Comparative Analysis (fsQCA) method, this paper further explored the influencing factors configuration affecting the CCD of GSTIE and DEL. The research results are as follows. Compared with the development of green science and technology innovation, the development of the digital economy was relatively backward. The CCD between China's provincial GSTIE and DEL showed an overall increasing trend year by year, and there was obvious spatial heterogeneity in which the eastern region was the highest, followed by the western and central regions. A single influencing factor does not constitute a necessary condition for a high CCD. There were four paths that improve the coordinated development level between GSTIE and DEL: HC+RD+OP-jointly driven, RD+OP-dual driven, HC+GS-dual driven, and GS-oriented. Finally, based on the research conclusions, this paper proposed corresponding policy suggestions.